Effects of transaction costs on rice farmers' adoption of certified seeds in the Philippines - Cuevas, Agham C. (Journal of Economics, Management & Agricultural Development, 2016)
The paper uses pooled data consisting of 1,816 farm households to determine the effects of transaction costs and other factors on the adoption and level of utilization of certified seeds. The model was estimated using Cragg's double hurdle estimator. Results show that transaction costs generally affect the probability of adoption but not the level of usage of certified seeds. Policies that can mitigate transaction costs can increase the adoption rate but other interventions are needed to improve the level of use of certified seeds of those who are already using them and those that are prospectively going to utilize them.